A Work in Progress: Unraveling the lessons learned in a co-teaching pilot - Hartnett, Mary Joanie; McCoy, Ann; Weed, Rahila; Nickens, Nicole (Educational (Re)naissance, 2014)
Colleagues at a midwestern university implemented a multi-semester co-teaching pilot for student teaching, and based on the data collected, are moving toward full implementation in the spring of 2015 for all pre-service teachers in the College of Education (COE). Part of the study replicated work conducted by St. Cloud University (Bacharach & Heck, 2011) and utilized that university’s evaluation instruments. However, the lessons learned in the pilot reveal some of the still “unanswered” questions as to how to ensure the quality and effectiveness of the co-teaching model during student teaching. Researchers share results and insights, and suggest action steps for full implementation of the co-teaching model.